ADVERTISEMENTS AND ITS RELATION WITH THE VIOLATION IN SOCIAL NETWORK - Majeed, Mohammed Fareed (International Journal of Research -GRANTHAALAYAH, 2021)
In this research paper, the historical sequence of the start of advertisements and the intervals that went through were studied, the effect of advertising in promoting ideas, commodities and production. Hence, we divided the advertisement according to the historical stage and this division was also linked to the emergence of the Internet, as advertisements were described and analyzed before and after the emergence of the Internet, the issue of violations was also discussed, especially after the emergence of the Internet, where there were violations on the personal, social and even governmental levels, also the effect on promoting the goal of the advertisement were discussed also.